1994
DOI: 10.1007/bf00599236
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the relation between oxygen uptake and heart rate during different styles of aerobic dance and a traditional step test in women

Abstract: The oxygen uptake and heart rate in various styles of dance and in a graded step test have been compared in ten healthy women aged [mean (SD)] 34 (5) years. Dance was choreographed into progressively more energetic sequences typical of community classes, and videotaped. Oxygen uptake was assessed using a respirometer carried in a back-pack. Each of the two tests (dance and step) took 15-20 min and measurements were made in randomised balanced order on the same day. The mean oxygen costs of dance ranged from 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…As with the other comparative studies into HIP and LIP routines in exercise to music classes (Otto et al 1986;Williford et al 1989;Bell 1993) the present study has demonstrated that LIP popmobility represents a reduced metabolic demand when compared with its HIP counterpart. Therefore, keeping at least one foot on the¯oor at all times, as in the LIP session, represents a signi®-cantly lower metabolic challenge than when the body is lifted o the ground, even if this is only a small height, as in the HIP session.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…As with the other comparative studies into HIP and LIP routines in exercise to music classes (Otto et al 1986;Williford et al 1989;Bell 1993) the present study has demonstrated that LIP popmobility represents a reduced metabolic demand when compared with its HIP counterpart. Therefore, keeping at least one foot on the¯oor at all times, as in the LIP session, represents a signi®-cantly lower metabolic challenge than when the body is lifted o the ground, even if this is only a small height, as in the HIP session.…”
Section: Discussionmentioning
confidence: 52%
“…Therefore, heart rate in a LIP pomobility session may have only limited potential as an appropriate measure of exercise intensity. Bell (1993) states that it is likely that any discrepancy in training outcomes in aerobic dance studies is the result of reported training intensities having been overestimated. She states that the ®ndings of her study demonstrate that such an overestimation may not necessarily be derived from a disproportionate relationship between heart rate and O 2 , but because the majority of aerobic dance studies have relied upon pulse palpation as a means of monitoring and reporting training intensity, and she has shown pulse palpation to be unreliable.…”
Section: Discussionmentioning
confidence: 97%
“…One of them is the structure of the lesson. According to Bell and Bassey (1994), exercise intensity can be objectively infl uenced by the addition of arm work during workout, by the cadence of the music or by the number of high impact elements in the choreography. Aerobic dance composed entirely of high impact elements is more intensive, which is better for increasing physical fi tness (Grant, Davidson, Aitchison, & Wilson, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…According to Heinonen et al (1996), exercise consisting of only high impact elements may help decrease the risk of onset osteoporosis in later life. In light of the higher risk of injuries to legs, hips, and the lower back it is preferable to use low impact elements in aerobic dance (Bell & Bassey, 1994;Grand et al, 1998). Regarding to the fact that women, who took part in this study, were middle aged, slightly overweight, untrained and sedentary, aerobic dance composed mainly of low impact elements (even if the intensity is lower) was suitable for them and according to some authors should also improve aerobic capacity (Bell & Bassey, 1994;Grand et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation